Analyzing Verbal Interactions of an Autistic Student Teacher During ELT Practicum Using FIACS and its Impact on Speaking Skills - Saputri, Tiyas; Anam, Syafiul; Munir, Ahmad; Khan, Aslam (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study identifies the types of verbal interactions employed by an autistic student teacher during an English Language Teaching (ELT) practicum, as categorized by the Flanders Interaction Analysis Coding System (FIACS), and examines their impact on students’ speaking skills. Method: The method used was a descriptive qualitative method with a case study approach. The subject of the study was a student teacher with ASD who practiced ELT practicum in the real classroom in the eight grade of inclusion class at SMPN 39 Surabaya. The ELT practicum was conducted on May-September 2023. Data collection technique used in this study was observation, video recording and interview. To analyse the data from the observation, the data were processed into FIACS sheet and calculated to find the dominant type. From the video recording, the data were transcribed in the form of description and narration. Interview data were processed using descriptive qualitative. Results: All types of verbal interaction exist in the classroom. From the results of the FIAC matrix sheet, the most dominant types are students talk (initiation and response) because they have the highest percentage. The teacher’s verbal interaction with the students in the classroom has an effect on the development of the students’ English skills. There is no study that investigates the the autistic student teacher’s types of verbal interaction in the classroom in English Language Teaching (ELT) practicum, mostly the previous researches investigated the classroom interaction of the student teacher with a normal condition. The implication of this study suggests a research focus on how an autistic student teacher communicates verbally during his ELT practicum which can be analyzed using FIACS. This study is among the first to explore the verbal interaction patterns of an autistic student teacher using FIACS, highlighting the potential for inclusive pedagogical competence in ELT practicum settings.